The Social Life of the European Crisis: A Multilevel Analysis of Youth, Employment and the Economy of Wellbeing 2007–2012 - Antti Veilahti (Turku Centre for Welfare Research, 2022)
The economic crisis in Europe is often viewed as a continuation of the global financial crisis. However, it appears that the prolongation of the banking crises in the EU was catalyzed by real economic problems, like high unemployment rates, which were growing already before the global downturn. Multilevel methods are used to construct a more diffuse understanding of the European crisis, combining the European Quality of Life Survey with national statistics. The analysis suggests that there are two partially overlapping crises in Europe: the young, often viewed as being at the eye of the crisis, are burdened by unemployment in those countries suffering from the public financing problems. In contrast, where higher education is more common, the young are deprived and insecure. The paper demonstrates that this two-fold nature of the crisis has not been properly acknowledged by the public while national policies could have even deepened the crisis.